Vibrações e estabilidade paramétrica de cascas axissimétricas - Loula, Abimael Fernando Dourado (1979)
The general problem of Dynamics of Elastic Bodies is presented, and the problems of dynamic response and stability of rotating axisyrnmetric shells, under a non-rotating load, are studied. Using a Fourier series expansion for the circunferential variable it is shown that this load generates a periodic excitation on the shell. Linear and non-linear transient responses are then obtained through a finite difference approximation in the time domain anda finite element discretization in the longitudinal direction. The steady-state periodic solution is determined. Its infinitesimal stability is studied and the first approximation of parametric resonance regions is explicity derived.